2009
DOI: 10.1111/j.1742-1241.2009.02012.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of biphasic insulin aspart 30/70 (NovoMix®30) when switching from human premix insulin in patients with type 2 diabetes: subgroup analysis from the 6-month IMPROVE™ observational study

Abstract: Aims:IMPROVE™ is an open-label, multinational, non-randomised, 26-week observational study designed to evaluate the safety and effectiveness of biphasic insulin aspart 30 (BIAsp 30) in routine clinical practice. Here, we report data for patients switching to BIAsp 30 from human premixed insulin.Methods:Patients (n=3856) with type 2 diabetes previously receiving human premixed insulin with or without oral antidiabetic drugs were eligible for inclusion. Demographic data, efficacy end-points (HbA1c, fasting blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 24 publications
8
28
3
Order By: Relevance
“…Rates of hypoglycemia were, unsurprisingly, increased in treatment-naïve subjects following introduction of insulin (minor hypoglycemia from 0.54 to 2.61 events/patient-year); however, switching to BIAsp 30 in the insulin-treated group resulted in a decrease in hypoglycemia (8.11 to 3.23 events/patientyear). Data from the subgroup of 3,856 subjects receiving human premixed insulin at baseline indicate that switching to biphasic analogue resulted in a 1.8% reduction in HbA 1c and a decrease in minor hypoglycemia from 7.7 to 2.0 events per patient per year [28]. Similar findings emerged from the PRESENT study, a large observational study in almost 22,000 patients with T2D.…”
Section: Premixed (Biphasic) Analoguessupporting
confidence: 69%
“…Rates of hypoglycemia were, unsurprisingly, increased in treatment-naïve subjects following introduction of insulin (minor hypoglycemia from 0.54 to 2.61 events/patient-year); however, switching to BIAsp 30 in the insulin-treated group resulted in a decrease in hypoglycemia (8.11 to 3.23 events/patientyear). Data from the subgroup of 3,856 subjects receiving human premixed insulin at baseline indicate that switching to biphasic analogue resulted in a 1.8% reduction in HbA 1c and a decrease in minor hypoglycemia from 7.7 to 2.0 events per patient per year [28]. Similar findings emerged from the PRESENT study, a large observational study in almost 22,000 patients with T2D.…”
Section: Premixed (Biphasic) Analoguessupporting
confidence: 69%
“…This finding is not inconsistent with Boehm et al's study, which reported that premixed insulin analogue was associated with a significantly lower incidence of major hypoglycaemia in comparison with premixed human insulin (6). Additionally, the IMPROVE study had also reported a reduction in hypoglycaemia upon shifting uncontrolled diabetes mellitus patients from premixed human insulin to premixed insulin analogue (10).…”
Section: Discussioncontrasting
confidence: 41%
“…Although most clinical trials demonstrate at least equivalent efficacy of analogues relative to human insulin, with additional benefits in terms of better postprandial glycaemic control, flexible injection timing and improvement in adherence (6)(7)(8)(9)(10), many of these trials did not consider the ethnic variations and the difference in eating habits of the study population. For instance, people in the Middle East, including Jordanians, usually have 3 main meals a day, with a relatively high calorie intake at lunch.…”
Section: Introductionmentioning
confidence: 99%
“…With shorter follow-up intervals of two to four weeks and faster and more effective titration of the insulin regime, the glycaemic control could be improved. Besides, modern insulin analogues that are premixed, such as Novormix or Humalog mix, should be considered for those diabetes patients with poor sugar control from human insulin, as they have been shown to provide better glycaemic control (14).…”
mentioning
confidence: 99%